Cross-Amplification in Strigiformes: A New STR Panel for Forensic Purposes - Patrizia Giangregorio (MDPI AG, 2021)
Strigiformes are affected by a substantial decline mainly caused by habitat loss and destruction, poaching, and trapping. Moreover, the increasing trend in bird trade and the growing interest in wild-caught rather than captive-bred birds are expected to encourage illegal trade. The biomolecular investigation represents a valuable tool to track illegal trade and to explore the genetic variability to preserving biodiversity. Microsatellite loci (STRs) are the most used markers to study genetic variability. Despite the availability of species-specific microsatellite loci in Strigiformes, a unique panel permitting the description of the genetic variability across species has not been identified yet. We tested 32 highly polymorphic microsatellite markers to evaluate the reliability of a unique microsatellite panel in different species of Strigiformes and its use for conservation and forensic purposes. We included in the study 84 individuals belonging to 28 parental groups and 11 species of Strigiformes. After screening polymorphic microsatellite loci, the description of genetic variability, and the kinship assessment, we characterized a final panel of 12 microsatellite loci able to identify individuals in 9 Strigiformes species. This STR panel might support the authorities in the forensic investigation for suspected smugglers and false parental claims; moreover, it can be useful to evaluate relatedness among individuals in captive-bred populations and to implement research projects finalized to the description of the genetic variability in wild populations.